1997
DOI: 10.1073/pnas.94.6.2626
|View full text |Cite
|
Sign up to set email alerts
|

A genetic system for Archaea of the genus Methanosarcina : Liposome-mediated transformation and construction of shuttle vectors

Abstract: New methods that allow, for the first time, genetic analysis in Archaea of the genus Methanosarcina are presented. First, several autonomously replicating plasmid shuttle vectors have been constructed based on the naturally occurring plasmid pC2A from Methanosarcina acetivorans. These vectors replicate in 9 of 11 Methanosarcina strains tested and in Escherichia coli. Second, a highly efficient transformation system based upon introduction of DNA by liposomes has been developed. This method allows transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
279
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 246 publications
(292 citation statements)
references
References 31 publications
2
279
1
Order By: Relevance
“…For example, mcrB uses a GTG start site, while frhA (encoding a hydrogenase subunit) and pta (encoding phosphotransacetylase) use TTG start sites (Bokranz and Klein 1987, Latimer and Ferry 1993, Vaupel and Thauer 1998. At least one gene, the repA gene of the pC2A plasmid, is predicted to utilize a CTG translation start (Metcalf et al 1997). Thus, we were interested in determining the relative efficiency of different start codons in Methanosarcina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mcrB uses a GTG start site, while frhA (encoding a hydrogenase subunit) and pta (encoding phosphotransacetylase) use TTG start sites (Bokranz and Klein 1987, Latimer and Ferry 1993, Vaupel and Thauer 1998. At least one gene, the repA gene of the pC2A plasmid, is predicted to utilize a CTG translation start (Metcalf et al 1997). Thus, we were interested in determining the relative efficiency of different start codons in Methanosarcina.…”
Section: Discussionmentioning
confidence: 99%
“…with autonomously replicating plasmid vectors (Metcalf et al 1997); however, this approach often introduces experimental artifacts owing to the higher plasmid copy number. For example, we have found that transformation can be difficult, or impossible, with plasmids carrying genes encoding membrane proteins or highly expressed reporter gene fusions.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo testing of these putative functional roles for Ech has not previously been possible because of a lack of methods for genetic analysis of Methanosarcina species; however, recent advances in the field now make such a study feasible (17)(18)(19)(20). In this report, we describe construction and characterization of an M. barkeri mutant lacking Ech.…”
mentioning
confidence: 99%
“…This problem has been alleviated somewhat in recent years by the development of genetic tools for use in members of the two distantly related genera, Methanococcus and Methanosarcina. These tools include selectable markers for genetic crosses (4-7), methods for high efficiency transformation (8,9), plasmid shuttle vectors (8,10), and methods for gene replacement (4,11,12) (the latter only in Methanococcus species). Despite these advances there continues to be a need for development of new tools for genetic analysis of methanoarchaea.…”
mentioning
confidence: 99%